2006
DOI: 10.1111/j.1440-1681.2006.04418.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sucralfate, Cimetidine and Rabeprazole on Mucosal Hydroxyproline Content in Healing of Ethanol–hcl‐induced Gastric Lesions

Abstract: 1. No general consensus has been reached on the treatment of acute gastric lesions. The aims of the present study were to clarify the effects of sucralfate, cimetidine and rabeprazole monotherapies and combination therapies on acute gastric lesions from the viewpoint of connective tissue regeneration. 2. Gastric lesions were experimentally created by the oral administration of 50% ethanol-0.15 mol/L HCl to rats. After 30 min, the anti-ulcer agents sucralfate (100 mg/kg), cimetidine (20 mg/kg) and rabeprazole (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…This increase in gastric hydroxyproline was reduced but not normalized by MethyB. Other researchers found increased hydroxyproline in gastric mucosa 2 and 4 h after intragastric administration of 50% ethanol-0.15 M HCl to rats compared with the untreated gastric mucosa [57]. We also showed that Na + -taurocholate resulted in extensive decrease in PAS + surface epithelial cells and gastric glands, indicating depletion of gastric mucus.…”
Section: Rossupporting
confidence: 51%
“…This increase in gastric hydroxyproline was reduced but not normalized by MethyB. Other researchers found increased hydroxyproline in gastric mucosa 2 and 4 h after intragastric administration of 50% ethanol-0.15 M HCl to rats compared with the untreated gastric mucosa [57]. We also showed that Na + -taurocholate resulted in extensive decrease in PAS + surface epithelial cells and gastric glands, indicating depletion of gastric mucus.…”
Section: Rossupporting
confidence: 51%
“…When we compared to the control value, Cc significantly inhibited ulcerative lesions in all doses, but the best result was obtained after pretreatment with Cc using the absolute ethanol model (Table 1). EtOH-induced ulcers are not inhibited by antisecretory agents such as cimetidine, but are inhibited by agents that exhibit a gastroprotective action with an anti-oxidative cytoprotection (Arisawa et al, 2006). Therefore, our results suggest that Cc has an antiulcerogenic effect related to cytoprotection.…”
Section: Resultsmentioning
confidence: 72%
“…[4] показали важливість оксипроліну як одного з основних маркерів ульцерогенезу за умов водно-іммобілізаційного стресу. Тоді як інші автори [18] відмічають необхідність колагену у клітинній диференціації та швидкості гоєння виразкових уражень при етаноліндукованому ульцерогенезі. Отже, меланін може виступати важливим елементом захисту структурної цілісності СОШ за умов дії стресу різного генезу.…”
Section: результати та їх обговоренняunclassified